17β-Estradiol/N-acetylcysteine interaction enhances the neuroprotective effect on dopaminergic neurons in the weaver model of dopamine deficiency. (21st April 2016) - Botsakis, K.; Theodoritsi, S.; Grintzalis, K.; Angelatou, F.; Antonopoulos, I.; Georgiou, C.D.; Margarity, M.; Matsokis, N.A.; Panagopoulos, N.T.
Highlights: Co-administration of 17β and NAC is efficient to block the degeneration of DA neurons. 17β/NAC synergism enhances neuroprotection of DA neurons " in vivo ". The antioxidant effect of 17β is enhanced in the presence of NAC (glutathione precursor). Abstract: The weaver mouse, is a phenocopy of Parkinson's disease (PD) in which dopaminergic neurons degenerate gradually during development, reaching at P21 a neurodegeneration of 55%. Thus, the weaver mouse constitutes an appropriate in vivo PD model for investigating the effect of neuroprotective agents. In the present study, long-term treatment (from P1 to P21) with 17β-estradiol (17β-estradiol) significantly protected the dopaminergic neurons in the substantia nigra (SN) of weaver mouse by 54%, as was detected by immunohistochemical experiments, using the specific antibody against tyrosine hydroxylase (TH). This dopaminergic neuroprotection is in line with our biochemical results showing that 17β-estradiol treatment significantly decreased the high lipid peroxidation levels seen in the SN of weaver mouse, indicating high oxidative stress. Interestingly, co-administration of 17β-estradiol with N-acetylcysteine (NAC, precursor molecule of glutathione (GSH)) further significantly increased the survival of dopaminergic neurons in the SN (by 85%), with a parallel further decrease of lipid peroxidation to normal levels. Our results show the in vivo neuroprotective effect of 17β-estradiol, which is strongly enhanced by co administration of NAC, indicating a strong synergistic effect of the two drugs. Furthermore, the main mechanism underlying this neuroprotective action seems to be the reversal of the oxidative stress shown by the high peroxidation levels. These results could be of clinical relevance since both drugs are already used separately in the clinic, 17β-estradiol for treatment of PD and NAC as a mucolytic agent and for the treatment of several disorders.